2011
DOI: 10.1179/174329211x12968219310792
|View full text |Cite
|
Sign up to set email alerts
|

Protein tyrosine phosphatase alpha regulates cell detachment and cell death profiles induced by nitric oxide donors in the A431 human carcinoma cell line

Abstract: We investigated the role of protein tyrosine phosphatase-alpha (PTPα) expression in the cell death profile of the A431 human carcinoma cell line that was induced by cytotoxic concentrations of the nitric oxide (NO) donors sodium nitroprusside (SNP) and 3,3-bis-(aminoethyl)-1-hydroxy-2-oxo-1-triazene (NOC-18). Both NO donors promoted extensive cell detachment in A431 parental cells as compared to the detachment observed for A431 cells that ectopically expressed PTPα (A431 (A27B(PTPα)) cells). The NO-induced cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…NO plays a crucial role in the signal transduction pathway involved in cell proliferation, survival, and cell death in almost all types of cells 51,52 . Additionally, NO is a well-known critical factor involved in inflammatory responses in many types of cells, including macrophages 53,54 .…”
Section: Discussionmentioning
confidence: 99%
“…NO plays a crucial role in the signal transduction pathway involved in cell proliferation, survival, and cell death in almost all types of cells 51,52 . Additionally, NO is a well-known critical factor involved in inflammatory responses in many types of cells, including macrophages 53,54 .…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic expression of RPTPa in these cells was shown to switch the mechanism of cell death from apoptosis to necrosis (19). The same group reported that another NO donor, SNAP, stimulated cell proliferation in fibroblasts expressing RPTPa while promoting growth arrest in cells with deleted RPTPa gene (18).…”
Section: No-induced and Rptpa-mediated Cell Deathmentioning
confidence: 86%
“…[13,38] NO is not restricted to pro-tumor effects, since NO can also promote anti-tumor actions. [2,39,40] Nitrosative stress conditions resulting from an activated immune response or exposure to high concentrations of nitrosylating agents lead to cancer cell death. [7,39] Therefore, concentrations of NO, time of exposure, and cell sensitivity to the radical determine the NO-mediated course of action in tumor cells.…”
Section: Nitric Oxide and Cancer: A Two-way Streetmentioning
confidence: 99%
“…[2,39,40] Nitrosative stress conditions resulting from an activated immune response or exposure to high concentrations of nitrosylating agents lead to cancer cell death. [7,39] Therefore, concentrations of NO, time of exposure, and cell sensitivity to the radical determine the NO-mediated course of action in tumor cells. [13,41] Low to intermediate concentrations of NO/ RSNO stimulate oncogenic signaling pathways…”
Section: Nitric Oxide and Cancer: A Two-way Streetmentioning
confidence: 99%
See 1 more Smart Citation